Launch of the on-line archive of the Journal of the Statistical and Social Inquiry Society of Ireland, 1847-2007; followed by an address by Aidan Punch - O'Brien, Miriam Hederman; Punch, Aidan (Statistical and Social Inquiry Society of Ireland, 2007)
The journals of the Statistical and Social Inquiry Society of Ireland provide a remarkable record of both the events and the ideas of the past 160 years. They relate mainly to Ireland but they reflect the views and enthusiasms that swept through Britain, Europe and the rest of the world.
Read the 16th May 2007
Keywords: Online access; Statistical and Social Inquiry Society of Ireland; Archive; 314.15